Aplikasi teknik rangkaian neural dalam capaian teks - Mat Yamin, Fadhilah; Siraj, Fadzilah; Sheikh Osman, Wan Rozaini (Universiti Utara Malaysia, 2003)
Efective information retrieval is a major requirement for most users. This is because too much information limits the current search engine capability in filtering the document. Therefore, this paper discussed the applications of Artificial Intelligence in information retrieval system. The application of Artificial Intelligence techniques in information retrieval will produce an intelligent information retrieval system to enhance the retrieval processes. In addition, a model for intelligent information retrieval system is also discussed.